Dark triad personality dan kualitas kehidupan kerja karyawan yang bekerja secara hybrid: Kepemimpinan empowering sebagai mediator: Dark triad personality and quality of work life of hybrid employees: Empowering leadership as a mediator - Wati, Rinda Kumala; Indrayanti, Indrayanti (Persona:Jurnal Psikologi Indonesia, 2024)
The COVID-19 pandemic has made changes to various sectors, including ways of working that are now more widely adopting a hybrid model, which has an impact on the quality of an individual's work life. A supervisor's personality and leadership style play an important role in this. The purpose of this study is to empirically measure the role of empowering leadership as a mediator between the dark triad personality and the supervisor's leadership style. as a mediator between the personality of the dark triad and the quality of work life of hybrid employees. employees who work in a hybrid manner. Data were collected online from 217 employees from various agencies and positions, using a purposive sampling method. The data collection method uses three types of scales, namely the quality of work-life scale (α=0.861), the short dark triad personality scale (α=0.849), and the empowering leadership scale (α = 0.91). Data were analyzed using mediation analysis using JASP 0.16.2.0 software. The results of data analysis show that empowering leadership can significantly mediate the relationship between narcissistic personality and psychopath personality on the quality of work life. Empowering leadership does not have a mediating effect on the Machiavellian personality and the quality of work life. This research in organizations implies that the perception of the quality of work life of employees with narcissistic and psychopathic personalities can be changed through the role of leaders who have an empowering leadership style.